Aquaponics Food Production Systems 2019
DOI: 10.1007/978-3-030-15943-6_22
|View full text |Cite
|
Sign up to set email alerts
|

Aquaponics as an Educational Tool

Abstract: This chapter provides an overview of possible strategies for implementing aquaponics in curricula at different levels of education, illustrated by case studies from different countries. Aquaponics can promote scientific literacy and provide a useful tool for teaching the natural sciences at all levels, from primary through to tertiary education. An aquaponics classroom model system can provide multiple ways of enriching classes in Science, Technology, Engineering and Mathematics (STEM), and the day-today maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Combined circular food systemsaquaculture and plant production together in the same systemare entirely new in the perspective of food production techniques and can also be implemented widely in education and knowledge transfer (Junge et al 2019). In Norway, researchers have focused on the development of recirculating aquaculture systems (RAS) during the past 30 years, and the production of the most salmonids fingerlings grow in land-based RAS.…”
Section: Education and Knowledge Transfermentioning
confidence: 99%
“…Combined circular food systemsaquaculture and plant production together in the same systemare entirely new in the perspective of food production techniques and can also be implemented widely in education and knowledge transfer (Junge et al 2019). In Norway, researchers have focused on the development of recirculating aquaculture systems (RAS) during the past 30 years, and the production of the most salmonids fingerlings grow in land-based RAS.…”
Section: Education and Knowledge Transfermentioning
confidence: 99%
“…98,99,165 Low water use and the possibility to be adopted as a tool to promote educational, cultural, leisure and tourism values, and landscape improvement are positive aspects usually linked to aquaponics systems. 39,105 For biofloc-based production, Belettini et al 166 evaluated the carbon footprint of commercial shrimp production using LCA and showed that electricity is also a key impacting factor in BFT, while feed has a minor impact. Sustainability assessments of FLOCponics systems were not found in the literature.…”
Section: Sus Tainab Ilit Y a S Pec Tsmentioning
confidence: 99%
“…For aquaponics production, studies using LCA have shown that the main environmental impacts of aquaponics are related to infrastructure, electricity and feed 98,99,165 . Low water use and the possibility to be adopted as a tool to promote educational, cultural, leisure and tourism values, and landscape improvement are positive aspects usually linked to aquaponics systems 39,105 . For biofloc‐based production, Belettini et al 166 evaluated the carbon footprint of commercial shrimp production using LCA and showed that electricity is also a key impacting factor in BFT, while feed has a minor impact.…”
Section: Sustainability Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cities also utilise large quatities of water, create an enormous quantity of waste and pollute the air. Climate changes are predicted to cause more environmental stressors in the future, while we need to intensify food production ( Junge & Graber 2014). The required transition will need increased flexibility of the urban environment, more sustainable use and re-use of natural resources as well as the adaptation of infrastructure systems (Herrera-Gomez et al 2017).…”
Section: Introductionmentioning
confidence: 99%